2022
DOI: 10.1007/s00109-022-02244-w
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin receptor 3E variant is a risk factor for female IBS-D

Abstract: Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT3 receptor family. 5-HT3Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT3R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Rather, we revealed that the 5-HT4R/cAMP/PKA pathway negatively regulated ileal glucose absorption, consistent with previous reports that cAMP/PKA inhibited NHE3 to regulate SGLT1 activity in mouse ileum [37,25,24]. High levels of 5-HT in the gastrointestinal tract are associated with diarrhea-related celiac disease, irritable bowel syndrome, and carcinoid syndrome [7,13]. 5-HT has a propulsive effect on the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, we revealed that the 5-HT4R/cAMP/PKA pathway negatively regulated ileal glucose absorption, consistent with previous reports that cAMP/PKA inhibited NHE3 to regulate SGLT1 activity in mouse ileum [37,25,24]. High levels of 5-HT in the gastrointestinal tract are associated with diarrhea-related celiac disease, irritable bowel syndrome, and carcinoid syndrome [7,13]. 5-HT has a propulsive effect on the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a serotonin receptor 3E variant was recently implicated as a risk factor for female IBS-D subjects who exhibited downregulated transcript levels in the colon. 64 Interestingly, Htr1b – a similar serotonin receptor – was significantly downregulated in the E. coli microtype in this study and was a predicted target of multiple miRNAs, such as miR-29a-3p. Further, tachykinin family members Tac3 and Tac1 (a substance P precursor closely associated with regulation of gastrointestinal motility, secretion, and pain sensitivity), and the miRNAs miR-17-5p, miR-423-5p, miR-324-3p and miR-99a-3p (predicted to interact with pain-associated targets) were dysregulated in both the Desulfovibrio and E. coli microtypes, suggesting that pain-related pathways might be a common signature in both microtypes.…”
Section: Discussionmentioning
confidence: 58%